The strain-rate and temperature dependence of the mechanical properties of polyetherketone and polyetheretherketone - Hamdan, Sinin; Swallowe, G. M. (Springer, 1996)

(untitled)
ABSTRACT The mechanical properties of polyetheretherketone and polyetherketone were studied as a function of strain rate and temperature in the ranges 10⁻3 to 103s⁻1 and 20–200°C. At temperatures below the glass transition temperature, Tg, the strain-rate sensitivity of both polymers was found to be almost independent of temperature with a value of ̴4 MPa per decade of strain rate and the behaviour was well described by an Eyring relationship leading to an activation volume of ̴1 nm3. Above Tg, X-ray and differential scanning calorimetry studies show that cold-crystallization phenomena play a very important part in the polymer behaviour, leading to an increase of yield stress with increasing temperature. The crystallization was found to be highly strain-rate dependent with no increase in crystalline content occurring in quasi-static tests and increases of up to 20% in higher rate tests. Much of the data have been gathered using novel test equipment which is described in the paper.